Species of sand flies (Diptera: Psychodidae) collected from natural reserves in the Pacific and Darien regions of Colombia - Rafael J. Vivero; María Angélica Contreras; Juan D. Suaza; Iván D. Vélez; Charles Porter; Sandra Uribe (Biomédica: revista del Instituto Nacional de Salud, 2017)
Introduction: The departments of Chocó and Antioquia in Colombia show climatic and vegetation conditions favoring the establishment of vector species of the genus Lutzomyia and the transmission of Leishmania spp. to human populations entering conserved forest environments. Objective: To report the species of Phlebotomine sandflies present in three natural reserves in the Darien and Pacific regions of Colombia. Materials and methods: Sand flies were collected specifically in the natural reserves El Aguacate (Acandí, Chocó), Nabugá (Bahía Solano, Chocó) and Tulenapa (Carepa, Antioquia). Sand flies were collected with CDC light traps, active search in resting places and Shannon traps. The taxonomic determination of species was based on taxonomic keys. For some species of taxonomic interest, we evaluated the partial sequences of the 5’ region of COI gene. Results: A total of 611 adult sand flies were collected: 531 in Acandí, 45 in Carepa and 35 in Bahía Solano. Seventeen species of the genus Lutzomyia, three of the genus Brumptomyia and one of the genus Warileya were identified. The genetic distances (K2P) and grouping supported (>99%) in the neighbor joining dendrogram were consistent for most established molecular operational taxonomic units (MOTU) of the Aragaoi group and clearly confirmed the identity of Lu. coutinhoi. Conclusion: Species that have importance in the transmission of leishmaniasis in Acandí, Bahía Solano and Carepa were identified. The presence of Lu. coutinhoi was confirmed and consolidated in Colombia.